Identifikasi Plasma Nutfah Kedelai Berumur Genjah dan Berdaya Hasil Tinggi - I Made J. Mejaya; Ayda Krisnawati; Heru Kuswantoro (Buletin Plasma Nutfah, 2010)
Identification of Early Maturing and High Yielding Soybean Germplasm. Preference to early maturing soybeans is higher than the late ones, since early maturing soybean can improve planting index and able to escape from fail of harvest due to drought stress. To identify accessions of soybean germplasm which will be used as gene resources in developing of early maturing and high yielding varieties, a numbers of 203 soybean germplasm accessions were evaluated at Jambegede Research Station on dry season 2006. Observation primarily conducted on physiological maturity and flowering date. Beside, observation also conducted on plant height, number of branches, 100 seeds weight and seed yield. Result showed that accession of MLGG 0751 and MLGG 0753 identified having early maturity (70 days). The early maturing accessions had lower yield than the late maturing ones. There was no accession having both of early maturing and high yielding traits. Accessions of MLGG 0751 and MLGG 0753 can be used as gene resources in developing of early maturing varieties. AbstrakPreferensi terhadap kedelai berumur genjah lebih tinggi daripada berumur dalam karena kedelai berumur genjah dapat meningkatkan indeks pertanaman dan dapat menghindari kegagalan panen akibat cekaman kekeringan. Untuk mengidentifikasi aksesi plasma nutfah yang akan digunakan sebagai sumber gen dalam perakitan varietas kedelai berumur genjah dan berdaya hasil tinggi, sebanyak 203 aksesi plasma nutfah kedelai dievaluasi di Kebun Percobaan Jambegede pada musim kemarau 2006. Pengamatan terutama dilakukan terhadap umur masak fisiologis dan umur berbunga. Pengamatan juga dilakukan terhadap tinggi tanaman, jumlah cabang, bobot 100 biji, dan hasil biji tanaman. Hasil penelitian menunjukkan bahwa aksesi MLGG 0751 dan MLGG 0753 teridentifikasi berumur genjah (70 hari). Aksesi berumur genjah memiliki hasil biji lebih rendah daripada aksesi berumur dalam. Tidak diperoleh aksesi kedelai berumur genjah yang sekaligus berdaya hasil tinggi. Aksesi MLGG 0751 dan MLGG 0753 dapat digunakan sebagai sumber gen dalam perakitan varietas kedelai berumur genjah.